2022
DOI: 10.3389/fbioe.2022.941826
|View full text |Cite
|
Sign up to set email alerts
|

Modified Mineral Trioxide Aggregate—A Versatile Dental Material: An Insight on Applications and Newer Advancements

Abstract: Mineral Trioxide Aggregate (MTA) has been a material of revolution in the field of dentistry since its introduction in the 1990s. It is being extensively used for perforation repairs, apexification, root-end filling, obturation, tooth fracture repair, regenerative procedures, apexogenesis, pulpotomies, and as a pulp-capping material because of its desired features such as biocompatibility, bioactivity, hydrophilicity, sealing ability, and low solubility. Even though its application is wide, it has its own draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Bioceramic materials such as mineral trioxide aggregate (MTA) have also been reported as pulp‐capping material in clinical treatment (Bernabé et al., 2007; Giuliani et al., 2002; Rodrigues et al., 2017). However, the further application of these bioceramic materials in dental practice is challenging because of their high cost and possible tooth discoloration (Ioannidis et al., 2013; Pushpalatha et al., 2022). Consequently, developing novel anti‐inflammatory pulp‐capping agents with excellent dentine regenerative properties is of considerable clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Bioceramic materials such as mineral trioxide aggregate (MTA) have also been reported as pulp‐capping material in clinical treatment (Bernabé et al., 2007; Giuliani et al., 2002; Rodrigues et al., 2017). However, the further application of these bioceramic materials in dental practice is challenging because of their high cost and possible tooth discoloration (Ioannidis et al., 2013; Pushpalatha et al., 2022). Consequently, developing novel anti‐inflammatory pulp‐capping agents with excellent dentine regenerative properties is of considerable clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MTA has many advantages such as antibacterial properties and ability to aid in the release of bioactive dentin matrix proteins [5,6]. However, some disadvantages such as high solubility [5,7], long setting time, and poor handling properties [8] are still ascribed to this cement. To overcome some drawbacks of bioceramics, especially to improve the handling characteristics and to decrease solubility, the polymers were added.…”
Section: Introductionmentioning
confidence: 99%
“…The first commercial product of endodontic HCSC, grey ProRoot MTA (Dentsply, Tulsa, OK, USA), was launched in 1998. Subsequently, a tooth-colored variant, white ProRoot MTA (PR; Dentsply), was developed by reducing the iron oxide content of grey ProRoot MTA and was introduced to the market in 2002 [1]. A number of in vitro and in vivo investigations have shown that PR exhibits excellent biocompatibility, hard-tissue inductivity, and sealing capacity in the presence of moisture (such as blood and tissue fluids) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%